2014
DOI: 10.1247/csf.14009
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and Characterization of Sweat Gland Myoepithelial Cells from Human Skin

Abstract: ABSTRACT. Stem cells routinely maintain the main epidermal components, i.e. the interfollicular epidermis, hair follicles, and sweat glands. Human sweat glands present throughout the body are glandular exocrine organs that mainly play a role in thermoregulation by sweating. Emerging evidence points to the presence of stem cells in sweat glands, but it remains unclear whether such stem cells exist in human sweat glands. Here, we attempted to gather evidence for stem cells in human sweat glands, which would be c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
21
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 28 publications
1
21
0
Order By: Relevance
“…Rittie et al reported that duct cells in human sweat glands contribute to re-epithelialization of the skin after trauma [23]. We have previously shown that myoepithelial cells are enriched with sweat gland stem cells possessing the ability to regenerate sweat gland-like spheres with apical and basal cell layers that express luminal (K8) and myoepithelial (αSMA) markers, respectively [24, 25]. We also revealed that myoepithelial cells including stem cells are closely surrounded by neighboring nerve fibers, indicating that sweat gland stem cells reside in a unique environment.…”
Section: Discussionmentioning
confidence: 99%
“…Rittie et al reported that duct cells in human sweat glands contribute to re-epithelialization of the skin after trauma [23]. We have previously shown that myoepithelial cells are enriched with sweat gland stem cells possessing the ability to regenerate sweat gland-like spheres with apical and basal cell layers that express luminal (K8) and myoepithelial (αSMA) markers, respectively [24, 25]. We also revealed that myoepithelial cells including stem cells are closely surrounded by neighboring nerve fibers, indicating that sweat gland stem cells reside in a unique environment.…”
Section: Discussionmentioning
confidence: 99%
“…Human eccrine sweat gland epithelial cells have also been shown to regenerate epidermis during skin wound healing . Human eccrine gland stem cells have not yet been characterized in detail, but myoepithelial cells were suggested to be the progenitor cells .…”
Section: Regulation Of Eccrine Sweat Gland Developmentmentioning
confidence: 99%
“…Each eccrine sweat gland unit consists of two portions, the secretory coil and the duct, which differ in morphology and function (Figure 2A) [55, 56]. The secretory coil contains acinar epithelial cells (that can be divided further into clear and dark cells) surrounded by myoepithelial cells, whereas the duct is composed by two layers of cuboidal epithelium [55].…”
Section: Mechanism Of Salt and Fluid Secretion In Eccrine Sweat Glmentioning
confidence: 99%
“…Modified from [56]. The enlargement on the right shows a crossection through the secretory coil portion of an eccrine sweat gland.…”
Section: Figurementioning
confidence: 99%